1997
DOI: 10.1103/physrevb.56.9744
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Laue dynamical theory for x-ray reflectivity at low and high incidence angles on strained multilayers

Abstract: In this work, we present a generalized dynamical theory for strained multilayers within the Laue formalism valid for x-ray Bragg diffraction. In the generalized theory we take into account all the four solutions of the secular equation, the asymptotic sphericity of the dispersion surface, the difference between electric and displacement fields, and the boundary conditions of continuity at the heterointerfaces for the tangential components of the electric and magnetic fields. Only the following approximations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Using GDT [16] (for the (004) reflection) it was found that the peak positions coincide very closely with those from Bragg's condition…”
Section: Large Angle Diffraction Scansmentioning
confidence: 61%
See 1 more Smart Citation
“…Using GDT [16] (for the (004) reflection) it was found that the peak positions coincide very closely with those from Bragg's condition…”
Section: Large Angle Diffraction Scansmentioning
confidence: 61%
“…Improved treatments of the deviation to higher order than in the original formulation of Takagi-Taupin [4] have been recently presented [14,15]. In [16] a generalized DT (GDT) has been presented in which the only approximations are the two-beam case and the neglection of higher powers of the dielectric susceptibility. It is claimed that this model allows to describe the interaction of the X-ray beam with strained heterostructures in the whole angular range 0 to pa2 [16].…”
Section: Comparison Of Akt and Dynamical Diffraction Theorymentioning
confidence: 99%
“…The position for the zeroth-order satellite peak can be estimated from Eq. (1) by setting m ¼ 0 and from this, the average indium composition is calculated [10]. The thickness of the constituent layers in the period is now estimated using the growth rates of GaAs and InGaAs determined from RHEED oscillations.…”
Section: Resultsmentioning
confidence: 99%
“…4a) consists of a narrow substrate peak and several satellite peaks at angles smaller than the substrate Bragg angle. Using the kinematical approximation, the thickness of the superlattice period and the average alloy composition can be estimated by using the following relationship [10]:…”
Section: Resultsmentioning
confidence: 99%
“…The exact solution of dispersion equation and complete matrices ͑33͒ have to be used for the grazing-incidence ͑-exit͒ geometry, 14 and for the diffraction from superlattices with short period, when satellite peaks are located far from the exact Bragg condition. 15 The numerical problems arise for superlattices with large number of periods N, where multiple production of (4ϫ4) matrices has to be done. 14 These problems are caused by operations with matrices, the elements of which grow exponentially with the increasing value of N. In order to avoid these difficulties, new algorithm was suggested in Ref.…”
Section: Mew For High-resolution X-ray Diffraction From Superlattmentioning
confidence: 99%